Between the Unknown and the Emergence of Psychotherapeutic Research Questions (Existential Analysis: Journal of the Society for Existential Analysis, 2004)
This article explores an alternative way of looking at the generation of research questions whereby they can emerge from experience and the unknown, thus the researcher's experience in psychotherapeutic research is highlighted, not as a background to the research but as a vital element of the research. It will be argued that psychotherapeutic research is an intersubjective process and as such questions surface between a series of relationships; in psychotherapeutic research we need to consider, therefore, the speaking subject as always speaking to the other, as subject to the other. It will be argued that Continental philosophy leads to an opening up of this space between rather than concocting a story to fit a particular epistemology. The space between leads to possibility and the unknown in research and learning from experience which in turn generates anxiety leading to difficulties in speaking of experience. Thus through a series of disparate experiences an attempt is made to create a clearing and question why we tend to seek closure, enclosure rather than abiding with the unknown which becomes a focus for research. The phenomenology of Merleau Ponty is seen as a phenomenology of relations that neither assimilates nor rejects the other, but holds a tension between.